Preconcentration and Determination of Mercury(II) using Modified Silica Gel with Diphenylthiocarbazone by Cold Vapour Atomic Absorption Spectrometry - Moghimi, Ali; Javad Poursharifi, Mohammad (Asian Journal of Chemistry, 2011)
A simple and fast method for extraction and determination of trace amounts of mercury(II) ions using silica gel bound amines phase modified with diphenylthiocarbazone (DPC). Silica gel bound amines phase modified with diphenylthiocarbazone (SG-DPC) was prepared based on chemical immobilization technique. The product (SG-DPC) was used as an adsorbent for the solid phase extraction Hg(II) prior to their determination by cold vapour atomic absorption spectrometry (CV-AAS). The uptake behaviours of SG-DPC for extracting Hg(II) ions were studied using batch and column procedures. For the batch method, the optimum pH rang for Hg(II) extraction was 2.5-7. For enrichment and determination of Hg(II) on the newly designed adsorbent, the pH value if 4.0 was selected. Hg(II) ion can be desorbed with 2 mL of 0.5 mol L-1 of HCl. The results indicate that SG-DPC has rapid adsorption kinetics using the batch method. The adsorption capacity for Hg(II) ion is in the 1.3 mmol g-1, with a high enrichment factor of 125. The presence of commonly coexisting ions does not affect the sorption capacities. The limit of detection of the proposed method is 7 ng/mL. The relative standard deviation (RSD) of the method under optimum conditions was 4 % (n = 8) for Hg(II). The method is applied to the recovery of Hg2+ from different synthetic samples and water sample.